FIELDimageR.Extra: Advancing user experience and computational efficiency for analysis of orthomosaic from agricultural field trials - Popat S. Pawar; Filipe Inacio Matias (Plant Phenome Journal, 2023)
Abstract FieldimageR.Extra is an advanced R package that enhances user experience and computational efficiency in analyzing orthomosaic images from agricultural field trials. Through the integration of modern GIS libraries like terra, stars, and sf, it surpasses traditional packages like raster and sp. The FieldimageR.Extra offers interactive visualization, vector feature creation, and spatial data editing within the R environment through the integration of mapview and mapedit packages. Notably, FieldimageR.Extra introduces new functions like fieldShape_render and fieldShape_edit, enabling flexible plot grid generation and editing capabilities. Comparative evaluations demonstrate the superior performance of FieldimageR.Extra in handling spatial data, crop and extract operations, and plot grid generation. With its comprehensive features, FieldimageR.Extra stands as a valuable addition to the FieldimageR R package, offering researchers efficient tools for unmanned aerial vehicle‐based orthomosaic image analysis in agricultural research. FIELDimageR.Extra is publicly available as a GitHub repository (https://github.com/filipematias23/FIELDimageR.Extra).